Peranan Koperasi terhadap Penurunan Biaya Transaksi Usaha Ternak Sapi Perah di Kabupaten Boyolali - Aini, Anis Nur; Syaukat, Yusman; Rifin, Amzul (Jurnal Agro Ekonomi, 2016)
EnglishBoyolali Regency is the largest milk-producer in Central Java Province. There are many market institutions serving the farmers in selling their products. Interaction between the dairy-cow farmers and market institutions incurs transaction costs. The farmers’ efforts to reduce risk of milk quality deterioration and to search market institutions create transaction costs resulting in profit reduction. Objective of this study is to analyze the transaction costs paid by the dairy-cow farmers. Transaction cost was computed using an accounting approach and its determinants were evaluated using a regression method. Primary data were collected through a survey conducted in Cepogo District, Boyolaly Regency, during April-May 2016 from 104 farmer respondents.The results showed that average transaction cost was Rp47,44/liter. Total monthly transaction costs paid by the village cooperative (KUD) members were Rp31.955, consisted of searching cost (Rp1.059 or 3.31%), negotiation cost (Rp724 or 2.27%), and enforcement cost (Rp30.173 or 94.42%). Total monthly transaction costs paid by the non-KUD members were Rp48.012 per month, consisted of Rp2.825 (5.88%), Rp1.204 (2.51%), and Rp43.983 (91,61%) for searching cost, negotiation cost, and enforcement cost, respectively. Transaction cost paid by the KUD members were lower than that paid by non-KUD members. Roles of cooperative in reducing transaction costs were not determined by membership status, but by its real services as reflected in increasing the number of cows per farm, shorter distance of the cooling unit to the farms and information provision to all members.IndonesianKabupaten Boyolali merupakan penghasil susu terbesar di Provinsi Jawa Tengah. Terdapat beberapa lembaga pemasaran yang bekerja sama dengan peternak dalam penjualan susu. Upaya peternak untuk mengurangi risiko susu cepat rusak dan mencari lembaga pemasaran akan memunculkan biaya transaksi yang menurunkan pendapatan peternak. Tujuan penelitian ini adalah untuk menganalisis biaya transaksi yang ditanggung peternak. Biaya transaksi dihitung dengan metode akuntansi, sementara determinan biaya transaksi ,dianalisis dengan metode regresi. Data dikumpulkan melalui survei di Kecamatan Cepogo, Kabupaten Boyolali selama bulan April hingga Mei 2016 dengan jumlah responden sebanyak 104 peternak. Penelitian menunjukkan bahwa rata-rata biaya transaksi yang dikeluarkan peternak adalah Rp47,44/liter susu. Total biaya transaksi per bulan yang dikeluarkan peternak anggota Koperasi Unit Desa (KUD) adalah Rp31.955, yang terdiri dari Rp1.059 (3,31%) biaya pencarian informasi, Rp724 (2,27%) biaya negosiasi, dan Rp30.173 (94,42%) biaya pelaksanaan kontrak. Total biaya transaksi yang dikeluarkan peternak bukan anggota KUD adalah Rp48.012, yang terdiri dari Rp2.825 (5,88%) biaya pencarian informasi, Rp1.204 (2,51%) biaya negosiasi, dan Rp43.983 (91,61%) biaya pelaksanaan kontrak. Biaya transaksi yang ditanggung peternak anggota KUD lebih rendah dibanding peternak bukan anggota KUD. Peranan KUD dalam penurunan biaya transaksi tidak ditentukan oleh status keanggotaan melainkan jasa layanan riil yang tercermin dalam peningkatan jumlah ternak piaraan, penurunan jarak kandang ke pabrik pengolahan susu (cooling unit), dan penyediaan informasi bagi seluruh anggotanya.